2015
DOI: 10.1118/1.4905375
|View full text |Cite
|
Sign up to set email alerts
|

Output calculation of electron therapy at extended SSD using an improved LBR method

Abstract: The improved LBR method has been generalized to calculate the output factor of electron therapy at extended SSD. The percentage difference between the calculated and the measured output factors of irregularly shaped cutouts in a clinical useful SSD region was within 2%. Similar results were obtained for all available electron energies of both Varian 2100C and ELEKTA Synergy machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In our previous publications [12,13], we demonstrated that σ R (z) is dependent on the size of the cutout. By considering this size dependence of σ R (z), we illustrated a significant improvement in the accuracy of PDD and output factor calculations.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…In our previous publications [12,13], we demonstrated that σ R (z) is dependent on the size of the cutout. By considering this size dependence of σ R (z), we illustrated a significant improvement in the accuracy of PDD and output factor calculations.…”
Section: Introductionmentioning
confidence: 67%
“…In our previous publications [12,13] we calculated the percentage depth dose curves and output factors of irregular cutouts. In this article, we extended our work to calculate the relative dose distribution of irregular cutouts at d max .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The off-axis of this method could be developed for higher accuracy. In addition, several studies found that MCI is less accurate than Monte Carlo simulation for complex dose distributions and is recommended for one point secondary dose check or simple geometry dose verification [23,24].…”
Section: Resultsmentioning
confidence: 99%